Bacillus subtilis M6 improves intestinal barrier, antioxidant capacity and gut microbial composition in AA broiler - Ji, Linbao; Zhang, Lian; Liu, Hu; Shen, Jiakun; Zhang, Yu; Lu, Lin; Zhang, Xiujun; Ma, Xi (Frontiers in Nutrition, 2022)
Bacillus subtilis can secret a variety of substances to improve human and animal gut health via inhibiting the proliferation of pathogenic bacteria. In this study, a fast-growing and stress-resistant strain of Bacillus subtilis M6 (B. subtilis M6) were isolated, which showed a strong antibacterial activity to E. coli K88, S. typhimurium ATCC14028, and S. aureus ATCC25923 in vitro. In vivo studies showed that B. subtilis M6 can significantly improve the average daily gain (ADG) using an AA broiler model. Dietary B. subtilis M6 improved the intestinal morphology. The villus height of jejunum and ileum were significantly increased. The concentration of malondialdehyde (MDA) in the ileal mucosa was significantly reduced in B. subtilis M6 treatment group, which suggested the oxidative stress of the ileum was significantly relieved. Though the β diversity of treatments was not significantly, B. subtilis M6 improved the composition of intestinal microbes, especially at the level of caecum genus, the dominant genus was changed from Ruminococcus to Akkermansia, which indicated the change of intestinal carbohydrate nutrition. In conclusion, these data indicate that the B. subtilis M6 shows a probiotic potential to improve intestinal health via altering gut microbiota.